Pelatihan Pertolongan Pertama pada Kecelakaan (P3K) di Sekolah Menengah Pertama Kota Lubuklinggau - Aprilyadi, Nadi; Zuraidah, Zuraidah; Elviani, Yeni; Pastari, Marta (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2019)
Accident refers to an event that occurs unintentionally. For example, traffic accidents, accidents with sharp objects and so on. The word accident is taken from the root word accident. The addition of the affixes